The Activity of Facial Serum from Essential Oil of Nutmed Seed (Myristicae fragrans Houtt.) as an Antiacne Agent - Rina Kurniaty; Resmila Dewi Dewi; Risa Nursanty (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Acne is a chronic inflammatory dermatological condition affecting the pilosebaceous unit and is influenced by multiple etiological factors, one of which is bacterial colonization by Propionibacterium acnes. Nutmeg seeds have been recognized as a natural source of antibacterial agents, exhibiting stronger inhibitory activity against Gram-positive bacteria than Gram-negative strains. This antimicrobial potential is attributed to the presence of bioactive constituents, including essential oils, saponins, and alkaloids. The essential oil content of nutmeg seeds has been reported to range from approximately 2% to 16%, with an average value of around 10%.This study aimed to develop an optimized cosmetic formulation in the form of a facial serum incorporating nutmeg seed essential oil as an anti-acne agent. The quality of the formulated serum was assessed through a series of physicochemical evaluations, including organoleptic properties, homogeneity, pH, viscosity, adhesion capacity, emulsion type, and spreadability. Antibacterial efficacy was evaluated against P. acnes using the agar well diffusion method, with essential oil concentrations of 15%, 20%, 25%, and 30%. A serum base without essential oil served as the negative control, while a commercially available anti-acne serum containing erythromycin was used as the positive control.Statistical analysis using ANOVA demonstrated that all serum formulations were capable of inhibiting the growth of P. acnes. The inhibition zone diameters observed for formulations containing 15% (F1), 20% (F2), 25% (F3), and 30% (F4) essential oil were 19.50±0.5000 mm (strong activity), 21.16±0.2887 mm, 22.33±0.2887 mm, and 24.33±0.5000 mm (very strong activity), respectively. According to standard criteria for inhibition zone interpretation, formulations with essential oil concentrations of 15%, 20%, and 25% were categorized as Intermediate (I), exhibiting inhibition diameters within the range of 14–22 mm, whereas the 30% formulation was classified as Susceptible (S) due to an inhibition zone diameter of ≥23 mm.